2008
DOI: 10.1111/j.1365-2710.2008.00915.x
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbation of psoriatic skin lesions in a patient with psoriatic arthritis receiving adalimumab

Abstract: Patients initiated on adalimumab therapy should be closely monitored for the development of exacerbation of psoriasis. Clinicians should be aware of this rare adverse effect of this anti-TNF drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Replication rates of chlamydia trachomatis, a common aetiological agent in ReA, are thought to be inversely proportional to TNF levels. Three patients taking TNF blockers who presented with pustolosis were found to be positive for chlamydia trachomatis DNA in the affected skin [90]. Further study is needed to clarify whether the psoriasiform lesions occurring in patients on anti-TNF therapy may rather represent Keratoderma blenorrhagicum.…”
Section: Safetymentioning
confidence: 95%
“…Replication rates of chlamydia trachomatis, a common aetiological agent in ReA, are thought to be inversely proportional to TNF levels. Three patients taking TNF blockers who presented with pustolosis were found to be positive for chlamydia trachomatis DNA in the affected skin [90]. Further study is needed to clarify whether the psoriasiform lesions occurring in patients on anti-TNF therapy may rather represent Keratoderma blenorrhagicum.…”
Section: Safetymentioning
confidence: 95%
“…Exacerbation of psoriatic skin lesions in patients with psoriatic arthritis receiving treatment with adalimumab [9,10] and other anti-TNF agents [11] has been occasionally reported. The latency period (5 months) between the start of adalimumab and the development of paradoxical psoriasis in our patient is consistent with previous reports, but methotrexate withdrawal just prior to the start of the skin flare may have played a role.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, taking a careful medical history, superintend redundant medicine consumption and drug interaction are a critical step for prevention. There are many reports in the literature regarding the initiating, triggering and aggravated roles of drugs in psoriasis etiopathogenesis [1–8]. However, it is difficult to prove in an antidepressant receiving patient whether the stress or drug is a triggering factor.…”
Section: Introductionmentioning
confidence: 99%
“…Even biological agents, which have been reported as successful in psoriasis treatment in recent years, have also been reported that they may cause exacerbations of psoriasis lesions [8–11]. …”
Section: Introductionmentioning
confidence: 99%